Impact of Serum Platelet Count on Infertility in Polycystic Ovary Syndrome: A Retrospective Case-Control Study - Chen Liu; Hongxing Lin; Lifang Xue; Haihua Xu; Hui Zhong; Chengwen Que (Clinical and Experimental Obstetrics & Gynecology)
Background: This study intended to investigate the correlation between insulin resistance (IR) and coagulation parameters in women with polycystic ovary syndrome (PCOS) and their effects on infertility. Methods: We retrospectively included 380 PCOS patients and 143 healthy controls between January 2018 and January 2021. Clinical data, including age; body mass index; white blood cell (WBC), neutrophil (NE), lymphocyte (Lym), and platelet (PLT) counts; and D-dimer, plasma sex hormone, fasting blood sugar, and fasting insulin levels, were collected. The relationship between these markers and PCOS was assessed. Results: Elevated homeostatic model assessment of insulin resistance score was independently related to infertility in women with PCOS (odds ratio [OR] = 1.825, 95% confidence interval [CI]: 1.091–3.055, p = 0.022). WBC (7.29 [5.99–8.59] vs. 6.25 [5.33–7.40], p < 0.001), NE (3.91 [3.22–4.98] vs. 3.36 [2.62–4.51], p = 0.001), PLT (276 [244.5–317.5] vs. 251.5 [219.25–281.5], p < 0.001), and Lym (2.51 [2.02–3.11] vs. 2.08 [1.85–2.53], p < 0.001) counts, and D-dimer levels (0.22 [0.15–0.42] vs. 0.20 [0.12–0.31], p = 0.023) in the serum were markedly higher in PCOS patients with IR. Furthermore, multivariate logistic regression analysis revealed that increased serum PLT count (OR = 3.066, 95% CI: 1.052–8.939, p = 0.040) and BMI (OR = 5.06, 95% CI: 1.166–21.963, p = 0.030) were independently correlated with the risk of IR in PCOS patients. Moreover, increased PLT count was independently related to infertility (OR = 3.380, 95% CI: 1.272‒8.982, p = 0.015). Conclusions: Elevated PLT count serve as an independent responsible role for infertility in PCOS women with IR, which indicate that PLT count might be a potential predictive marker for infertility in PCOS women with IR.